Strengthening the case for intralymphatic immunotherapy. Issue 6 (10th December 2022) - Hoffmann, Hans Jürgen; Hviid-Vyff, Bjarke
Abstract : Purpose of review: Intralymphatic immunotherapy (ILIT) is a promising novel method of immunotherapy, that is short and convenient, and may be very effective. Results have been varied, and efforts to unravel the real value of the treatment are ongoing. Methods used to assess the effect in clinical trials have been so varied that it is difficult to compare studies with each other. Recent findings: Some advances have been made; the importance of injecting into the lymph node has been illustrated, and treatment with a range of medicines has proven to be successful. In meta-analyses the treatment has been shown to have no serious side effects and to be an effective short term desensitizing agent. Now it remains to be shown that ILIT also has long-term effects of tolerance. Preliminary data suggest that there is a long-term effect. Summary: Injecting allergen directly into a lymph node strengthens the protective immune response. ILIT is safe and induces desensitization and very likely also induces tolerance. Compliance will improve compared with other treatment forms. If ILIT holds its promise, it will become an attractive option for patients with allergy.